Effect of Preemergence Herbicides on the Recovery of Bermudagrass from Spring Dead Spot. Issue 1 (28th March 2013) - Beck, L. L.; Cooper, T.; Hephner, A. J.; Straw, C. M.; Henry, G. M.
Abstract : Field experiments were conducted in Texas to examine the recovery of a bermudagrass [ Cynodon dactylon × C. transvaalensis (L.) Pers.] fairway from spring dead spot (SDS) disease following preemergence (PRE) herbicide applications. In 2011 and 2012 bermudagrass recovery from SDS in the non‐treated check plots (46 and 59%, respectively) was similar to bermudagrass recovery in response to oxadiazon at 3.4 kg/ha (55 and 57%, respectively) 14 weeks after treatment (WAT). Pendimethalin at 2.5 kg/ha resulted in 33 to 38% bermudagrass recovery from SDS 14 WAT. In 2011, oryzalin (1.68 kg/ha), dithiopyr (0.56 kg/ha), prodiamine (0.73 kg/ha), and dimethenamid (1.68 kg/ha) applications resulted in 21 to 25% bermudagrass recovery from SDS 14 WAT. In 2012, bermudagrass exhibited similar recovery in response to prodiamine and oryzalin (24 and 26%, respectively), while response to dithiopyr and dimethenamid was 33 and 34%, respectively, 14 WAT. Bermudagrass exhibited the least amount of recovery (13 to 14%) in response to indaziflam at 0.035 kg/ha, regardless of year. Oxadiazon can be safely used as a PRE option when bermudagrass is recovering from SDS, while the use of oryzalin, prodiamine, dithiopyr, dimethenamid, pendimethalin, and indaziflam may limit recovery and further contribute to a weakened turfgrass system.